From Farm to Field: Spent Mushroom Substrate as Potential Anti-Fungal Agents and Plant Growth Enhancer - Yunisaastari, Rachmi; Putra, Ivan Permana (Departemen Biologi, Institut Pertanian Bogor, 2025)
Spent mushroom substrate (SMS) is a result of mushroom growing utilizing mushroom substrate media, such as substrate. Unhandled SMS garbage demands a subscription and poses an environmental risk. The SMS was obtained from oyster mushrooms (Pleurotus ostreatus) in Jonggol, Bogor, West Java, using a mixture of sawdust, lime, and bran. The purpose of this research was to examine the effects of using SMS as a planting medium and biofertilizer for the growth of maize (Zea mays), also on determining the optimum concentration of SMS as an anti-pathogen for the plant pathogens Fusarium oxysporum and Colletotrichum gloeosporioides. This research utilized a completely randomized design. The antifungal test results for SMS water extract against Fusarium oxysporum showed that the fungus was inhibited from growing at 60 to 100% extract concentrations. The use of SMS as a growing medium gave the best results on the growth of the number of plant leaves. Microscopic observation of the morphology of fungal pathogens Fusarium oxysporum and Colletotrichum gloeosporioides showed that there was damage to the structure of fungal hyphae in the treatment of SMS water extract with 100% extract concentration. SMS might offer an eco-friendly solution for enhancing agricultural productivity and promoting waste valorization in Indonesia.